Program Satuan Pendidikan Aman Bencana dalam Perspektif Teori Kognitif SosialProgram Satuan Pendidikan Aman Bencana dalam Perspektif Teori Kognitif Sosial - Widodo, Edi; Siti Irene Astuti Dwiningrum; Hastuti (Jurnal Pendidikan Geografi Undiksha, 2024)
The disaster-safe education unit program still has various obstacles in its implementation so that the main objectives of the disaster-safe education unit program have not been realized. The purpose of this research is to find solutions to obstacles to the implementation of the disaster safe education unit program in the perspective of social cognitive theory. This type of research is qualitative with a literature review data collection method. This research uses a type of realist review, because it wants to interpret the real conditions of disaster-safe education units and then provide reinforcement and/or solutions if weaknesses are found. The results showed that based on social cognitive theory, in order for the Disaster Safe Education Unit (DSEU) program to realize its main objectives, there needs to be mutual interaction between students' personal selves, the behavior of school leaders, teachers and parents, and the environment that represents disaster resilience. Because social cognitive theory believes that students will imitate the habits of school leaders, teachers and parents. Therefore, school leaders, teachers and parents who behave in a disaster resilient manner will be recorded and implemented by students. The results of students' recording of the behavior of teachers and parents, then supported by a disaster resilient environment, will produce a generation that is resilient to disasters.